2012
DOI: 10.1542/peds.2011-3402
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Adolescent Health Status of Extremely Low Birth Weight Children Born 1992–1995

Abstract: OBJECTIVES: To compare the self-reported health of extremely low birth weight (ELBW, <1 kg) adolescents with that of normal birth weight (NBW) controls and the children’s assessments of their general health at ages 8 versus 14 years. METHODS: One hundred sixty-eight ELBW children and 115 NBW controls of similar gender and sociodemographic status completed the Child Health and Illness Profile–Adolescent Edition at age 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 50 publications
(56 reference statements)
1
12
0
2
Order By: Relevance
“…These risk factors may result from the prematurity, including adverse prenatal environments with maternal health complications (fetal programming), and/or challenges in developing healthy diets, including food sensitivities and intolerances (Barbieri et al, 2009; Behrman & Butler, 2007; Kaseva et al, 2013; Silveira et al, 2012), food neophobia (Migraine et al, 2013) and fussy eating (Samara, Johnson, Lamberts, Marlow, & Wolke, 2010), which parallels avoidance of risk taking (Hack et al, 2012; Roberts et al, 2013) and sensation seeking (Alley & Potter, 2011; Allin et al, 2006; Pliner & Melo, 1997). Intrauterine growth restriction with or without prematurity is linked to greater preference for sweets (Ayres et al, 2012; Barbieri et al, 2009; Silveira et al, 2012), salty taste (Stein, Cowart, & Beauchamp, 2006) and lower affinity/intakes of protein-rich foods and fruits (Kaseva et al, 2013; Migraine et al, 2013) in children and higher intakes of carbohydrates (Barbieri et al, 2009) and lower intakes of fruits, vegetables (Kaseva et al, 2013) and alcohol (Cooke, 2004; Roberts et al, 2013) in adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These risk factors may result from the prematurity, including adverse prenatal environments with maternal health complications (fetal programming), and/or challenges in developing healthy diets, including food sensitivities and intolerances (Barbieri et al, 2009; Behrman & Butler, 2007; Kaseva et al, 2013; Silveira et al, 2012), food neophobia (Migraine et al, 2013) and fussy eating (Samara, Johnson, Lamberts, Marlow, & Wolke, 2010), which parallels avoidance of risk taking (Hack et al, 2012; Roberts et al, 2013) and sensation seeking (Alley & Potter, 2011; Allin et al, 2006; Pliner & Melo, 1997). Intrauterine growth restriction with or without prematurity is linked to greater preference for sweets (Ayres et al, 2012; Barbieri et al, 2009; Silveira et al, 2012), salty taste (Stein, Cowart, & Beauchamp, 2006) and lower affinity/intakes of protein-rich foods and fruits (Kaseva et al, 2013; Migraine et al, 2013) in children and higher intakes of carbohydrates (Barbieri et al, 2009) and lower intakes of fruits, vegetables (Kaseva et al, 2013) and alcohol (Cooke, 2004; Roberts et al, 2013) in adults.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we hypothesized that PT-adults would report greater preference for high fat/sweet/salty foods, lower preference for healthy foods, and less dietary restraint on eating. Consistent with risk avoidance (Allin et al, 2006; Hack et al, 2012), we hypothesized that PT-adults would report lowest affinity for sensation-seeking activities and foods. Finally, since environment influences early development (Bradley et al, 1994; M.…”
Section: Introductionmentioning
confidence: 99%
“…Description of the study characteristics, study population, type and measurement of behavior, relevant results and confounders results were adjusted for, sorted by energy balance-related behavior and determinant.* Same cohort (Helsinki Study of VLBW adults). † Same cohort.Abbreviations: BW—Birth weight; BWR—Birth weight ratio; BMI—Body Mass Index; LBW—Low birth weight; NBW—Normal birth weight; HBW—High birth weight; MET—Metabolic Equivalent Task; PA—Physical activity; SGA—Small for gestational age (birth weight < -2 SD); AGA—Appropriate for gestational age; LGA—Large for gestational age (birth weight > +2 SD); PI—Ponderal Index; GA—Gestational age; SES—Socio-economic status; VLBW—Very low birth weight (<1500g); MVPA—Moderate-to-vigorous physical activity; ELBW—Extremely low birth weight (≤800g[58] or <1000g[12]); IUGR—Intrauterine growth retardation; c.p.m.—counts per minute; SB—Sedentary behavior.…”
Section: Resultsmentioning
confidence: 99%
“…For example, some studies found a positive association of birth weight with PA[10], whereas others reported no associations[11], inverse associations[12], PA-specific associations[13], age-specific associations[14] or gender-specific associations. [15] Factors that may contribute to the equivocal association of perinatal growth with energy balance-related behavior include differences in study population, the severity of growth retardation in low birth weight subjects, methodology pertaining to data collection (such as use of questionnaires) and different types of PA studied.…”
Section: Introductionmentioning
confidence: 99%
“…(7) Others have chronicled the persistent effects of prematurity on adolescence and young adulthood. (8) It is these survivors of NICU care that account for 40% of children who have cerebral palsy (CP), (9) 25% of children with hearing impairment, (10) and 35% of those with vision impairment. (11) Infants born at the border of viability (between 22 and 25 weeks' gestation) seem to have similar rates of impairment and degree of impairment among survivors, (4)(12) but predicting long-term outcomes for the current cohort of preterm infants remains difficult.…”
Section: Introductionmentioning
confidence: 99%